Effect of passive temperature therapy of the femoral muscles on the countermovement jump performance - Lee, J.; Panday, S. B.; Byun, K.; Lee, J.; Hwang, J.; Moon, J. (Korean Journal of Sport Biomechanics, 2019)
Objective: The purpose of this study was to evaluate the effect of passive-acute temperature therapy of the femoral muscle and dynamic warm-up on the countermovement jump performance.